2016
DOI: 10.1007/978-3-662-47238-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Function Nodes in Chinese Syntactic Networks

Abstract: Abstract. Based on two syntactic dependency networks derived from two Chinese treebanks of different registers, a statistical study is conducted regarding word frequency and distributions. We chose three grammatical (function) words as our research objects and analyzed their network features, including degree, out-degree, in-degree, closeness, in-closeness, out-closeness and betweenness. Then we removed these three word nodes from the networks so as to see what consequences may follow in the number of vertices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Second, in terms of syntactic connectivity, highly connected words tend not to be interconnected (Ferrer i Cancho et al, 2004 ). In Chinese, function words, such as prepositions, conjunctions, and auxiliary and modal particles, are the most connected word types that do not form syntactic dependency among themselves and only act as intermediate words in a syntactic network (Chen and Liu, 2016 ). Chen and Liu ( 2016 ) found that the number of de (“of”) and zai (“in”) in writing production of CSL learners is higher than that in oral production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, in terms of syntactic connectivity, highly connected words tend not to be interconnected (Ferrer i Cancho et al, 2004 ). In Chinese, function words, such as prepositions, conjunctions, and auxiliary and modal particles, are the most connected word types that do not form syntactic dependency among themselves and only act as intermediate words in a syntactic network (Chen and Liu, 2016 ). Chen and Liu ( 2016 ) found that the number of de (“of”) and zai (“in”) in writing production of CSL learners is higher than that in oral production.…”
Section: Discussionmentioning
confidence: 99%
“…In Chinese, function words, such as prepositions, conjunctions, and auxiliary and modal particles, are the most connected word types that do not form syntactic dependency among themselves and only act as intermediate words in a syntactic network (Chen and Liu, 2016 ). Chen and Liu ( 2016 ) found that the number of de (“of”) and zai (“in”) in writing production of CSL learners is higher than that in oral production. In addition, degrees of de are higher than those of zai , which is also found in native the production of Chinese speakers (Chen and Liu, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diverse words lead to diverse nodes, which provides a new perspective for investigating the formation of the scale-free feature. Reference [21] compares the characteristics of three central nodes in syntactic networks and explains their difference in frequency and syntactic importance. After examining the local and global properties of verb nodes, ref.…”
mentioning
confidence: 99%